Structural Analysis and Conformational Dynamics of Short Helical Hyperphosphorylated Segments of Tau Protein (Sequence 254–290) in Alzheimer’s Disease: A Molecular Dynamics Simulation Study - Alipour, Mozhgan; Motavaf, Mahsa; Abdolmaleki, Parviz; Zali, Alireza; Ashrafi, Farzad; Safari, Saeid; Hajipour-Verdom, Behnam (Frontiers in Molecular Biosciences, 2022)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that its early diagnosis leads to a chance for successful treatment and decreases the side effects. Hyperphosphorylation of tau proteins is a pathological hallmark of AD that causes it to lose its attachment ability to the microtubules. Alteration of tau structure due to its hyperphosphorylation is an exciting challenge regarding AD treatments. Here, we aimed to examine the structural alterations of short helical segments of tau protein with one and three phosphorylated sites by molecular dynamics simulation. Results indicated that the interaction of two similar segments with three phosphorylated sites (P-Ser262, 285, 289) formed a compact and more stable structure than the one phosphorylated site complex (P-Ser262). Moreover, due to the high dynamics of the P-Ser262 complex, several structures were made with different conformational dynamics, but there was only one stable cluster of P-Ser262, 285, 289 complex during simulation. Generally, it is important to identify how structural features of segments in tau protein change when the phosphorylated sites increase from one to three sites and their effects on the formation of paired helical filaments for drug design and diagnostic biomarkers.